2016
DOI: 10.1016/j.physa.2016.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Setting the agenda: Different strategies of a Mass Media in a model of cultural dissemination

Abstract: Day by day, people exchange opinions about a given new with relatives, friends, and coworkers. In most cases, they get informed about a given issue by reading newspapers, listening to the radio, or watching TV, i.e., through a Mass Media (MM). However, the importance of a given new can be stimulated by the Media by assigning newspaper's pages or time in TV programs. In this sense, we say that the Media has the power to "set the agenda", i.e., it decides which new is important and which is not. On the other han… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…Finally, we consider that this work could be used as an starting point in developing data-driven mathematical models about the interaction between mass media and society, given the traditional approaches coming from statistical physics [41,42,43,44,45], where much of the models lack in being contrasted with real data. Future works may include a more systematic study and its extension to international media, a deeper study combining topic detection and sentiment analysis, and a more quantitative analysis about causality.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we consider that this work could be used as an starting point in developing data-driven mathematical models about the interaction between mass media and society, given the traditional approaches coming from statistical physics [41,42,43,44,45], where much of the models lack in being contrasted with real data. Future works may include a more systematic study and its extension to international media, a deeper study combining topic detection and sentiment analysis, and a more quantitative analysis about causality.…”
Section: Resultsmentioning
confidence: 99%
“…When the discussion is about a specific topic, this process can be modelled using one-dimensional approach based on classical models, as for instance the Deffuants model with continuous opinions [34], various extensions of the voter model [35,36], and the Sznadjs model [37,38]. On the other hand, when the intention is to model the whole agenda of a media outlet, typically a multidimensional approach is used based on Axelrod's model [9,10,39,40,41,42,43]. If it is intended to model opinion changes related to political positions, a bi-dimensional representation based in Nolan Charts political spectrum diagram [21,22] or Political Compass [19] could be used.…”
Section: The Modelmentioning
confidence: 99%
“…On another stream of research, computational models have been implemented in order to describe collective behaviour arising from interactions between Mass Media and the citizens [9,10,11], providing theoretical tools to understand micro to macro effects in this situations. Other approaches are based on the analysis of large amount of data coming from surveys, as in [12,13], from big data [14] or from online traffic [15], where the authors have shown that the relative change in the number of page views of a general Wikipedia page on the election day can offer a reasonable estimation of the relative change in turnout for that election at the country level.…”
Section: Introductionmentioning
confidence: 99%
“…The Axelrod model has subsequently been extended in a variety of ways, including the introduction of "mass media" or other external cultural influence [25][26][27][28][29], complex networks [30,31], coevolving networks [32,33], and agent migration [34,35]. Two important extensions to the model are nondyadic interactions [36][37][38] and noise [32,36,39,40].…”
Section: A Axelrod's Model Of Cultural Disseminationmentioning
confidence: 99%